Facts About Zinc - Linda B. Bobroff (EDIS)
Zinc deficiency can affect the immune system, cognitive function, and growth in children. Severe zinc deficiency can cause diarrhea, hair loss, poor appetite, skin disorders, impotence, and changes in taste. People who drink alcohol in excess are at high risk for zinc deficiency (and other health problems). This 2-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, July 2013.